Unhiding female characters in the parable of the sower Reimagining fields and farms - Toit, Charel D. du; Eck, Ernest van 1960- (2025)
This article employs an unhiding reading methodology to explore the presence of women in Luke’s agrarian parables, specifically focussing on the parable of the sower. By engaging with Van Eck’s research on the realistic reading of the parables in their 1st-century socio-economic context and implementing Du Toit’s unhiding reading, the authors argue that women, although not explicitly mentioned, would have been imagined as present, active and important participants in agricultural labour by the original hearers of these parables. Drawing on historical evidence of women’s involvement in textile production, fieldwork and harvest activities, the article challenges traditional androcentric interpretations and highlights the integral role of women in the parable of the sower, and other agrarian parables. Intradisciplinary and/or interdisciplinary implications: An unhiding reading will be suggested at the end of this article, an alternative reading aiming to offer a more comprehensive understanding of the parables, grounded in the lived realities of a 1st-century Mediterranean audience.
Keywords: 1st-century Palestine; Luke’s parables; agrarian parables; female labourers; Feminism; Gender Studies; parable of the sower; realistic reading; unhiding reading; Women in the Bible